THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY, PROFITABILITY, AND LIQUIDITY TOWARD TAX AGGRESSIVENESS IN FOOD AND BEVERAGES COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Meilani, Meilani; Angel, Angel (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2024)
This study examines the influence of Corporate Social Responsibility, Profitability, and Liquidity toward Tax Aggressiveness in food and beverages companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2022. The independent variables used in this study are Corporate Social Responsibility measured by Corporate Social Responsibility Disclosure Index (CSRI), Profitability measured by Return on Assets (ROA), and Liquidity measured by Current Ratio (CR). Tax Aggressiveness as the dependent variable is measured by Effective Tax Rate (ETR). This study employs quantitative research design and use the secondary data, which is published financial statement and sustainability report in Indonesia Stock Exchange and company’s official website. From the total population of 43 companies, 27 food and beverages companies are chosen as samples by using purposive sampling method, resulting in total of 54 observations. The data analysis method used is multiple linear regressions, processed through Statistical Product and Service Solutions 26 (SPSS 26). The result of this study reveals that corporate social responsibility (CSRI) and liquidity (CR) have no significant influences toward tax aggressiveness partially. Meanwhile, profitability (ROA) has significant influence towards tax aggressiveness. Simultaneously, these three independent variables have significant influence toward tax aggressiveness.